THE INTEGRATION OF ARTIFICIAL INTELLIGENCE IN THE ACTIVITY OF AGRICULTURAL FARMS: A NEED TO ENSURE SUSTAINABILITY - Mirela PLESA; Alina MARCUTA; Liviu MARCUTA; Ovidiu GUSAN (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Humanity is currently facing numerous challenges, one of the most important being that of ensuring food security, which is why agriculture is becoming one of the important branches of the economy of any country. Ensuring a sustained agricultural production, which meets both the requirements related to respect for the environment and sustainability, but also those related to food sufficiency, are aspects for which researchers are constantly looking for solutions, and the transition from traditional practices to the use of digitization, innovative technologies or of artificial intelligence, represent current and interesting topics, which is why we have the right to deepen this topic in the present work. The methodology used was based on one hand on the analysis of specialized studies, and on the other hand, quantitative research was employed for the analysis of statistical data, facilitating a detailed and substantiated understanding of the impact of AI in agriculture. This approach entailed collecting data using descriptive statistics, followed by meticulous processing and analysis of the information. It included calculating growth rates and thoroughly examining the results. These methods enabled the development of well-founded opinions, conclusions, and recommendations regarding the application of artificial intelligence in agriculture. Through this comprehensive analysis, valuable insights were gained to inform and guide the effective integration of AI technologies in the agricultural sector. The study revealed valuable insights into the benefits and challenges associated with AI in this field, which can aid in developing more efficient and sustainable agricultural practices. Evidence of the growing interest in this area includes the significant rise in investments in intelligent agricultural equipment and artificial intelligence, which surged from 1.7 billion dollars in 2019, to 4.9 billion dollars in 2021, being estimated to reach 9.6 billion dollars this year. At the same time, the conducted study also allowed us to identify the advantages and challenges facing agriculture in the adoption and implementation of digitization and artificial intelligence in specific activities.